hw2sol - APPM 4/5520 Solutions to Problem Set Two 1. Let y...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: APPM 4/5520 Solutions to Problem Set Two 1. Let y 1 = g 1 ( x 1 ,x 2 ) = x 1 / ( x 1 + x 2 ) and let y 2 = g 2 ( x 1 ,x 2 ) = x 1 + x 2 . Then x 1 = g- 1 1 ( y 1 ,y 2 ) = y 1 y 2 and x 2 = g- 1 2 ( y 1 ,y 2 ) = y 2- y 1 y 2 = y 2 (1- y 1 ) . X 1 ,X 2 iid exp(rate = ) f X 1 ,X 2 ( x 1 ,x 2 ) = 2 e- ( x 1 + x 2 ) I (0 , ) ( x 1 ) I (0 , ) ( x 2 ) The Jacobian of the transformation J = vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle x 1 y 1 x 1 y 2 x 2 y 1 x 1 y 1 vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle = vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle y 2 y 1- y 2 1- y 1 vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle = y 2 So, f Y 1 ,Y 2 ( y 1 ,y 2 ) = f X 1 ,X 2 ( g- 1 1 ( y 1 ,y 2 ) ,g- 1 2 ( y 1 ,y 2 )) | J | = 2 e- ( y 1 y 2 + y 2 (1- y 1 )) I (0 , ) ( y 1 y 2 ) I (0 , ) ( y 2 (1- y 1 )) | y 2 | = 2 y 2 e- y 2 I (0 , 1) ( y 1 ) I (0 , ) ( y 2 ) . Now we integrate out (or, see alternative to follow) the unwanted y 2 : f Y 1 ( y 2 ) = integraltext f Y 1 ,Y 2 ( y 1 ,y 2 ) dy 2 = integraltext 2 y 2 e- y 2 I (0 , 1) ( y 1 ) dy 2 = I (0 , 1) ( y 1 ) (2) integraltext 1 (2) 2 y 2 e- y 2 dy 2 = I (0 , 1) ( y 1 ) (2) 1 = I (0 , 1) ( y 1 ) (2- 1)! = I (0 , 1) ( y 1 ) . (The integral was 1 since it was the integral of the (2 , ) pdf.) Therefore Y = Y 1 unif (0 , 1) . Note: We did not have to do the above integration since the joint pdf for Y 1 and Y 2 factors into a y 1 part and a y 2 part. This means that they are independent and, as long as we can collect the constants in the right way, we will see a unif (0 , 1) pdf (in y 1 ) times a (2 , ) pdf (in y 2 ). Therefore, we can conclude directly that Y = Y 1 unif (0 , 1). 2. (a) f X 1 ( x 1 ) = integraltext - f X 1 ,X 2 ( x 1 ,x 2 ) dx 2 = integraltext x 1 2 e- x 1- x 2 dx 2 = 2 e- 2 x 1 x 1 was below x 2 , but when marginalizing out x 2 , we ran it over all values from 0 to and so there was no upper bound on x 1 . The final answer for the marginal pdf of X 1 is f X 1 ( x ) = 2 e- 2 x I (0 , ) ( x ) . That is, X 1 exp ( rate = 2). f X 2 ( x 2 ) = integraltext - f X 1 ,X 2 ( x 1 ,x 2 ) dx 1 = integraltext x 2 2 e- x 1- x 2 dx 1 = 2 e- x 2- 2 e- 2 x 2 x 2 was above x 1 , but since there was no lower bound (other than 0) on x 1 when marginalizing out x 1 , x 2 ends up going all the way from 0 to . The final answer for the marginal pdf of X 2 is f X 2 ( x ) = 2 e- x 2 (1- e- x 2 ) I (0 , ) ( x ) ....
View Full Document

Page1 / 8

hw2sol - APPM 4/5520 Solutions to Problem Set Two 1. Let y...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online